Analisis Statistik Kecemasan dan Kemampuan Dasar pada Ekstrakurikuler Basket Putra di SMA Negeri 1 Sukoharjo - Winata, Garin AJi; Dwijayanti, Karlina; Nugroho, Untung (MAN Insan Cendekia Jambi, 2025)
The purpose of this study is to examine and identify the levels of anxiety and basic basketball skills among male students participating in the basketball extracurricular at SMA Negeri 1 Sukoharjo. This research is expected that accurate data can be obtained regarding the relationship between anxiety levels and the mastery of fundamental basketball techniques among students. This study employs a descriptive statistical approach. The sampling technique used is total sampling, with data collected through an anxiety level test and a basic basketball skill assessment. Based on the results of the anxiety and basic skill assessments, the majority of participants were in the